Penerapan Public Speaking Pada Karang Taruna Desa Cupak - Irda Agustin Kustiwi; Shofianti Prisilia; Nur Rohmatul Fitriya; Mufidah Sahla Oktavianty; Nadia Novita Alifiah Putri (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
The purpose of Community Service Activities is to provide Public Speaking skills to residents and cadets of Cupak Village in the form of socialization. The results of this activity showed that before the implementation of Community Service, all members still did not master the material about Public Speaking, but after the implementation of the activity was carried out, the participants of this Community Service activity all residents and cadets from this cupak village had the ability on how to package good communication. So they are skilled when they are required to appear speaking in front of tourists. Because as one of the important components in religious tourism villages, cupak, jombang, every citizen and cadet reef must have a positive image in the eyes of tourists. In addition, public speaking can also be used to promote tourism potentials that have not been known to the general public. The method used is to provide training through the provision of Public Speaking material to cupak villagers and then discuss together related to existing problems.